Effect of Skipping Rope Training on Resting Heart Rate and Cardiorespiratory Endurance Among Soccer Players - Laishram Santosh Singh; Luikang Pungding; Waribam James Singh; Bojan Bjelica; Erick Burhaein; Milan Zelenovic (JUMORA: Jurnal Moderasi Olahraga, 2022)
The main purpose of the present study was to investigate the effect of skipping rope training on resting heart rate and cardio-respiratory endurance among soccer players. A total of forty male soccer players (age 19 – 24 years) were selected from Manipur University, Imphal, Manipur (India) who participated in the national-level competition. The subjects were randomly assigned into two equal groups, the experimental group (n=20) and the control group (n=20).  The groups were measured before the intervention with resting heart rate and cardio-respiratory endurance to find out the overall significant effect among soccer players. After the initial test, the subjects of the experimental group participated in a supervised skipping rope training program, where no special exercise was administered to the control group. Skipping rope training programs were carried out for a period of six weeks, five days of training (Monday to Friday), and 60 minutes for each session. The experimental group showed improved scores in resting heart rate and cardio-respiratory endurance compared to the control group (p<0.05). The mean of the resting heart rate for the pre-test and post-test of the experimental group were 58.60 and 56.45 respectively. The values of the cardio-respiratory endurance were 72.41 and 80.47 respectively. The significant improvement in skipping rope training of the experimental group might be due to the six weeks of the soccer players. Skipping rope trainprogramsgram significantly improved physiological variables such as resting heart rate and motor fitness variables such as cardio-respiratory endurance of the male soccer players. Keywords: Skipping rope training, Resting heart rate, Cardio-respiratory endurance, Soccer players